Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 7 - Exponential Functions - Chapter Review Exercises - Page 386: 10



Work Step by Step

Since $g(x)$ is the inverse of $f(x)$, then $g(8)=g(f(-1))=-1$ and hence $$g'(x)=\frac{1}{f'(g(x))}\Longrightarrow g'(8)=\frac{1}{f'(-1)}=\frac{1}{12}.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.